Current and predicted future distributions of wallabies in mainland New Zealand. Issue 1 (2nd January 2019) - Latham, A. David M.; Latham, M. Cecilia; Warburton, Bruce
ABSTRACT: Bennett's ( Notamacropus rufogriseus ) and dama ( N. eugenii ) wallabies have been increasing in numbers and distribution in mainland New Zealand. Here, we update their current distributions; estimate current rates of spread to predict their future distributions; and describe the extent of suitable habitat for each species. Current distributions based on breeding populations and probable distributions based on outlier confirmed sightings resulting from natural dispersal and illegal liberations suggest that Bennett's and dama wallabies currently occupy between 5322–15, 229 km 2 (532, 200–1, 522, 900 ha) and 1865–4126 km 2 (186, 500–412, 600 ha), respectively. In 50 years, best- and worst-case estimates predict that they could occupy as much as 5883–44, 226 km 2 (588, 300–4, 422, 600 ha) and 1912–40, 579 km 2 (191, 200–4, 057, 900 ha), respectively. Habitat suitability was predicted to be high in the North and South islands, except for areas of high elevation, intensive agriculture with limited woody vegetative cover and large urban centres. In the absence of widespread intensive control, the ranges currently occupied by Bennett's and dama wallabies are predicted to increase by up to 7- and 20-fold (respectively) in 50 years. As their distributions continue to expand, they will become more difficult to control and their impacts more widespread. We suggest that progressively containing wallabies within increasingly smaller distributions and reducing their numbers to minimise damage within those distributions should be considered the top management priorities. If progressive containment is feasible it could lead to eventual eradication.